Highly flexible solid oxide fuel cells using phase-controlled electrolyte support. Issue 13 (October 2022) - Won, Bo-Ram; Kim, Yo Han; Jo, Seungyeon; Myung, Jae-ha
Abstract: Flexible solid oxide fuel cells (SOFCs) have attracted increasing attention due to their excellent mechanical stability and lightness. An essential electrolyte material for developing highly flexible SOFCs is 3 mol% yttria-stabilized zirconia (3YSZ), but there remain some difficulties in its application to SOFCs. We report a phase-controlled, bendable, ultra-thin 3YSZ electrolyte with a thickness of ~22 µm, high flexural strength, and improved ohmic resistance that surpasses that of 8 mol% YSZ electrolytes. A flexible cell (total thickness < 60 µm) is fabricated through simple and reproducible methods such as tape casting and screen printing. The highest cell performance is achieved among the reported flexible SOFCs, with the maximum power density of 0.86 W cm −2 at 900 °C using conventional cermet electrodes, Ni-YSZ anode, and LSM-YSZ cathode. Our study provides a well-defined framework for developing flexible SOFCs as next-generation power sources for mobile devices with high volumetric power.